The Influence of Infrastructure Development on the Economic Growth of North Sumatra Province - Ambarita, Desi Sulastri; Hasyim, Sirozujilam; Sari, Raina Linda (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research analyzes the influence of infrastructure development and convergence on economic growth in North Sumatra Province which is divided into four regions, namely the east coast, west coast, highlands, and islands. The analysis uses the multiple panel data regression method with time series data for 2018-2022. The regression results show that the Gross Fixed Capital Formation (GFCF) variable has a positive and significant impact in the East Coast and highland regions, while in the West Coast and island regions it has a negative but significant impact. Average Years of Schooling (RLS) has a positive and significant impact in most areas, except in island areas where it is not significant. Electrical infrastructure has a positive and significant impact in all regions, road infrastructure has a positive and significant impact in the west coast and highland areas, and for the east coast and island regions, the impact is positive but not significant. Meanwhile, the impact of clean water infrastructure varies. σ-convergence was found only in the east coast region, while β-convergence was detected in all regions with different levels of convergence, but lagging districts/cities took a very long time to catch up with the growth of developing districts/cities with a half-life of 47 years in the east coast region. 82 years on the west coast, 19 years on the highland areas, and 29 years on the island areas.